Persistent Effect of Gait Exercise Assist Robot Training on Gait Ability and Lower Limb Function of Patients With Subacute Stroke: A Matched Case–Control Study With Three-Dimensional Gait Analysis - Wang, Yiji; Mukaino, Masahiko; Hirano, Satoshi; Tanikawa, Hiroki; Yamada, Junya; Ohtsuka, Kei; Ii, Takuma; Saitoh, Eiichi; Otaka, Yohei (Frontiers in Neurorobotics, 2020)
Introduction: No study has observed the persistent effect of GEAR training using 3D gait analysis. This matched case-control study assessed the durability of the effectiveness of gait training of patients with sub-acute stroke using Gait Exercise Assist Robot (GEAR). Methods: Gait data of ten patients who underwent GEAR intervention program and ten patients matched for age, height, sex, affected side, type of stroke, and initial gait ability who underwent conventional therapy were extracted from database. The outcome measures were Functional Independence Measure-walk (FIM-walk) score, Stroke Impairment Assessment Set total lower limb motor function (SIAS-L/E) score, spatiotemporal factors, and abnormal gait patterns at 3 time-points: baseline, at the end of intervention, and within 1-week before discharge. Results: In the GEAR group, the FIM-walk score, SIAS-L/E score, cadence and single stance time of paretic side at discharge were significantly higher than that at post-training (p<0.05), while the stance time and double support time of unaffected side, knee extensor thrust, insufficient knee flexion, and external rotated hip of the affected side were significantly lower (p<0.05). However, no significant differences in these respects were observed in the control group between the corresponding evaluation time-points. Conclusion: In patients with sub-acute stroke, GEAR training resulted in persistent improvement in gait ability and motor recovery after the intervention.